Inventory Policy Planning For Starter Pack Of Pt Xyz In Jabotabek Region Using Probabilistic Method : P Model With Variant Demand - Shaula Tiominar Rebecca; Budi Sulistyo; Efrata Denny Saputra Yunus (eProceedings of Engineering, 2015)
Abstract PT XYZ is the largest cellular telecommunications company in Indonesia. One of their products are starter pack. Starter pack is a package that designed to serve the start of a service, it contains many items that have been predetermined to be used according to the rules. Starter pack can be considered as the initial identity before performing communication. Starter pack contains a SIM card that will be used by the mobile phone user with bonus of phone credit, some basic rules such as how to reload your phone credit and checking the credit. In fulfilling the needs of its customers, PT XYZ divides the distribution of starter packs into 10 regions, namely Sumbagut, Sumbagsel, Sumbagteg, Jabotabek, West Java, Central Java, East Java, Balinusra, Borneo and Sulmarija. In order to fulfill the demand of starter pack, PT XYZ has a problem in inventory at Jabotabek region, there are inventory stock that not approach the sales, which causes too much inventory in the warehouse. The amounts of starter packs are available in the warehouse always exceeds the number of sales, resulted in a buildup of inventory in the warehouse. Excess inventory occurs because the determination of the amount of inventory is not good because in determining the amount of inventory, PT XYZ just do a prediction by looking at the amount of current inventory, demand planning and seeing the demand pattern of earlier periods. In order a starter pack to the central warehouse, PT XYZ, Jabotabek region order the starter pack on Monday in every week. PT XYZ have a policy that the service level must be 99.9983% without back order.This excess inventory can caused companies must spend a considerable cost. Based on these problems, a starter pack inventory management becomes one of the things, that is important for companies to be able to minimize inventory costs that must be spent by the company. In order to improve inventory policy of Starter pack, PT XYZ needs to be optimized in several ways, including amount of the maximum and minimum stock in inventory in order to minimize the total cost of inventory. Inventory policy planning in this research is using the P model (periodic review) with variant demand to make a good policy in PT XYZ when determine an inventory. Using P model (periodic review) with variant demand method this research can make an inventory policy with safety stock, maximum inventory, optimum quantity order and time for ordering while in the existing condition the company did not have and can minimize total inventory cost of stater pack as 32% or Rp.158.375.229 from existing condition. Carrying cost have saving Rp 158.497.769 or 24% from existing condition without shortage cost because in proposed condition does not experience a shortage inventory. In proposed condition order cost more expensive than the existing condition as Rp. 122.537. Key word: P model ( periodic review), Inventory Policy, Telecommunication Company in Indonesia